Antenatal Fetal Adrenal Measurements at 22 to 30 Weeks' Gestation, Fetal Growth Restriction, and Perinatal Morbidity - Blue, Nathan R.; Hoffman, Matthew; Allshouse, Amanda A.; Grobman, William A.; Simhan, Hyagriv N.; Turan, Ozhan M.; Parry, Samuel; Chung, Judith H.; Reddy, Uma; Haas, David M.; Myers, Stephen; Mercer, Brian; Saade, George R.; Silver, Robert M. (American Journal of Perinatology, 2019)
Objective Our objective was to test the association of fetal adrenal size with perinatal morbidity among fetuses with fetal growth restriction (FGR; estimated fetal weight [EFW] < 10th percentile).Study Design This was a secondary analysis of the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-be (nuMoM2b) adrenal study, which measured fetal adrenal gland size at 22 to 30 weeks' gestation. We analyzed the transverse adrenal area (TAA) and fetal zone area (absolute measurements and corrected for fetal size) and the ratio of the fetal zone area to the total transverse area using a composite perinatal outcome of stillbirth, neonatal intensive care unit admission, respiratory distress syndrome, necrotizing enterocolitis, retinopathy of prematurity, sepsis, mechanical ventilation, seizure, or death. Among fetuses with FGR, adrenal measurements were compared between those that did and did not experience the composite perinatal outcome.Results There were 1,709 eligible neonates. Seven percent (n = 120) were diagnosed with FGR at the time of adrenal measurement, and 14.7% (n = 251) experienced perinatal morbidity. EFW-corrected and absolute adrenal measurements were similar among fetuses with and without FGR as well as among those who did and did not experience morbidity. The area under the curve for corrected TAA was 0.52 (95% confidence interval 0.38–0.67).Conclusion In our cohort, adrenal size was not associated with risk of morbidity among fetuses with FGR.
Keywords: fetal growth restriction; perinatal morbidity; adrenal gland; placental insufficiency; prenatal ultrasound